2015
DOI: 10.1111/imj.12924
|View full text |Cite
|
Sign up to set email alerts
|

Hospital discharge summary scorecard: a quality improvement tool used in a tertiary hospital general medicine service

Abstract: We assessed the impact of completion and feedback of discharge summary scorecards on the quality of discharge summaries written by interns in a general medicine service of a tertiary hospital. The scorecards significantly improved summary quality in the first three rotations of the intern year and could be readily adopted by other units as a quality improvement intervention for optimizing clinical handover to primary care providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…However, it differs from the abovementioned approaches and other previously described curricular innovations centered around teaching trainees the essentials of discharge summary preparation or use of discharge summary scorecards. 8,16 The expected length of stay in our study did not improve, which was in opposition to our original hypothesis. We suspect this was because the models used already accounted for the variables documented with the discharge diagnosis template and the template did not include variables specific to expected LOS, as we had assessed the most common and highest weighted variables across the three domains of cost, LOS and mortality.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, it differs from the abovementioned approaches and other previously described curricular innovations centered around teaching trainees the essentials of discharge summary preparation or use of discharge summary scorecards. 8,16 The expected length of stay in our study did not improve, which was in opposition to our original hypothesis. We suspect this was because the models used already accounted for the variables documented with the discharge diagnosis template and the template did not include variables specific to expected LOS, as we had assessed the most common and highest weighted variables across the three domains of cost, LOS and mortality.…”
Section: Discussioncontrasting
confidence: 99%
“…However, it differs from the abovementioned approaches and other previously described curricular innovations centered around teaching trainees the essentials of discharge summary preparation or use of discharge summary scorecards. 8 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…17,18 Techniques employed have ranged from the provision of one-off and regular teaching sessions to clinicians through to programmes providing both teaching and feedback. [19][20][21][22][23] Importantly, it has been shown that the results of these QIPs can be long-lasting. 24 Additionally, the Royal College of Physicians has provided guidance on how to improve discharge summaries, which can be utilised when designing teaching on this subject.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, we found that discharge summaries prepared by fourth-year medical students demonstrated frequent errors and omissions, emphasizing the need for early, standardized education [6]. Published curricula have been feasible to implement and improved trainees' competence; however, programs have struggled with sustainability and delivery of personalized feedback [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%